An automated treatment planning strategy for highly noncoplanar radiotherapy arc trajectories - Carrasqueira, P. (2021)
Radiation therapy is a technology-driven cancer treatment modality that has experienced significant advances over the last decades, thanks to multidisciplinary contributions that include engineering and computing. Recent technological developments allow the use of noncoplanar volumetric arc therapy (VMAT), one of the most recent photon treatment techniques, in clinical practice. In this work, an automated noncoplanar arc trajectory optimization framework designed in two modular phases is presented. First, a noncoplanar beam angle optimization algorithm is used to obtain a set of noncoplanar irradiation directions. Then, anchored in these directions, an optimization strategy is proposed to compute an optimal arc trajectory. Treatment plans obtained considering the optimized noncoplanar arc trajectories, for a pool of twelve difficult head-and-neck tumor cases, present a remarkable quality improvement when compared with treatment plans obtained considering coplanar equispaced beam directions, still commonly used in clinical practice. Furthermore, significant quality improvements were obtained for some of the cases when compared to coplanar VMAT treatment plans. Automated procedures like the one proposed in this paper will simplify the current treatment workflow, making better use of human resources and allowing for unbiased comparisons between different treatment techniques. As running the proposed automated framework will not waste any human resources, it can be assessed as being a valuable tool in clinical practice even if it only benefits specific patients.